Pulmonary arterial hypertension associated with congenital heart disease: lessons learnt from the large Turkish Nationwide Registry (THALES). (1st June 2021) - Kücükoglu, Serdar M.; Kaymaz, Cihangir; Alehan, Dursun; Kula, Serdar; Akcevin, Atıf; Celiker, Alpay; Cicek, Sertac M.; Tokgözoglu, Lale S.; Kentli, Suleyman; ,
Abstract : Pulmonary hypertension is a group of diseases, including pulmonary arterial hypertension associated with congenital heart disease (APAH‐CHD), characterized by progressive deterioration in pulmonary hemodynamics associated with substantial morbidity and mortality risk. THALES is a national multicenter, prospective observational registry, providing data on patients with APAH‐CHD. The study comprised APAH‐CHD patients (>3 months of age) with confirmed diagnosis of right heart catheterization or echocardiographic findings. Initial and follow‐up data were collected via regular hospital visits. Descriptive statistics are used for definitive purposes. Overall, 1034 patients aged 3 months–79 years (median 11.2 [Q1–Q3: 2.2–24.3] years) with APAH‐CHD were enrolled at 61 centers, 50.3% being retrospectively enrolled. Most had either Eisenmenger's syndrome (49.2%) or systemic‐to‐pulmonary shunts (42.7%). Patients were mostly in functional class I–II at the time of diagnosis (46.6%). Mean 6‐min walk distance (6MWD) was 369 ± 120 m. Mean pulmonary arterial pressure was 54.7 ± 22.2 mmHg for the whole group, and was highest in patients with Eisenmenger's syndrome. Targeted therapies were noted in 398 (38.5%) patients (monotherapy in 80.4%). Follow‐up data were available in 506 patients. Survival at 140 months was 79% and was associated with baseline 6MWD >440 m ( p  = 0.009), brain natriuretic peptide level < 300 ng/L ( p  < 0.001). Follow‐up 6MWD >165 m ( p  < 0.0001), brain natriuretic peptide level <300 ng/L ( p  = 0.031), and targeted therapies ( p  = 0.004) were also predictive of survival. THALES is the largest registry dedicated to APAH‐CHD to date and provides important contributions on demographics, clinical characteristics, and gaps in disease management.